High-strength light-weight corrosion-resistant medium-manganese steel, and preparation method and application thereof

CN121718800BActive Publication Date: 2026-10-23HEBEI SPORTS SCIENCE INSTITUTE (ANTI DOPING SERVICE CENTER OF HEBEI SPORTS BUREAU) +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511928661.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-19
Publication Date
2026-10-23
Estimated Expiration
2045-12-19

AI Technical Summary

Technical Problem

[0007]针对现有临床常用的金属材料无法兼顾高强度、低模量、高耐蚀、轻量化等多重性能需求的问题,本发明提供一种高强轻量化耐腐蚀中锰钢及其制备方法和应用

Benefits of technology

[0044]第三方面,本发明还提供了上述高强轻量化耐腐蚀中锰钢在骨科内固定及植入材料领域中的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121718800B_ABST
    Figure CN121718800B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of metal materials, and particularly discloses a high-strength light-weight corrosion-resistant medium-manganese steel as well as a preparation method and application thereof. The microstructure of the medium-manganese steel is composed of a stable austenite framework and a fine-grained dual-phase layer through the synergistic micro-alloying design of Cu, Ti, Mo and V elements, combined with two-phase zone annealing and high-frequency pulse current treatment. The structure makes the material have high strength and high toughness, and also makes the elastic modulus of the material close to human bones through the retained large amount of metastable austenite, thereby effectively relieving the stress shielding effect. Finally, ultrasonic impact treatment is performed to introduce gradient nanostructures and residual compressive stress on the surface layer, thereby significantly improving the surface hardness, wear resistance and fatigue resistance. The medium-manganese steel prepared by the method has ultrahigh strength, good toughness, an elastic modulus close to human bones and excellent physiological corrosion resistance, and is particularly suitable for joint internal fixation devices subjected to complex stress.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metallic materials technology, and in particular to a high-strength, lightweight, corrosion-resistant medium-manganese steel, its preparation method, and its applications. Background Technology

[0002] Orthopedic internal fixation and implant materials, especially fracture fixation plates and screws used in joint areas (such as the knee, ankle, and elbow joints), are key instruments for treating fractures of joints and surrounding tissues. Because joints bear both weight and function, and require maintaining joint surface flatness and protecting surrounding soft tissues, implant materials must simultaneously meet multiple objectives, including high strength, appropriate elastic modulus, excellent corrosion resistance, and reasonable lightweighting.

[0003] Joint implants need to serve long-term under complex stress conditions. On the one hand, they must provide sufficient static load-bearing capacity to resist the loads generated by limb weight and muscle contraction (such as the force of 1 to 2 times body weight when the lower limb is standing). This requires materials with high tensile strength and yield strength to prevent fracture, bending, or "crushing" of fracture ends. On the other hand, the repetitive alternating loads (frequency of about 1 to 2 Hz) generated by joint movement pose a severe challenge to the dynamic fatigue strength of the materials. In addition, the elastic modulus of the material needs to be as close as possible to that of human cortical bone (about 100 to 120 GPa). If the elastic modulus is too high, it is easy to cause stress shielding effect, leading to disuse osteoporosis of the fixed bone due to insufficient mechanical stimulation, increasing long-term risks.

[0004] Human tissue fluid is rich in chloride ions (concentration approximately 0.9%~1.2%) and proteins. Furthermore, at different stages of wound healing, local pH, reactive oxygen species concentration, and immune responses are constantly changing. This environment continuously damages the passivation film on metal surfaces, inducing pitting corrosion, crevice corrosion, and a vicious cycle of corrosion-inflammation. Metal ions (such as Ni...) 2+ Cr 3+ The continuous leaching of ions can not only damage the structural integrity of materials, but also cause biocompatibility problems such as allergies and local toxicity. Therefore, higher requirements are placed on the corrosion resistance and ion release control of implanted materials.

[0005] Clinically, there is a significant contradiction between the need for lightweight implants and their mechanical reliability. While weight-reduction designs (such as thinning the wall thickness and using hollow structures) can reduce patient burden and soft tissue irritation, they often lead to a decrease in overall stiffness and strength, increasing the risk of bending or breakage under premature load. Simultaneously, inappropriate lightweight designs may cause localized stress concentration, accelerating fatigue failure, and even exacerbating stress shielding effects due to improper stiffness reduction. Therefore, how to achieve effective weight reduction while ensuring and improving the overall mechanical performance and long-term service reliability of implants is a critical challenge that urgently needs to be addressed in this field.

[0006] Currently, commonly used implantable metal materials such as 316L stainless steel, cobalt-chromium alloys, and titanium alloys cannot simultaneously meet the multiple requirements of high strength, low modulus, high corrosion resistance, lightweight, and high reliability. Therefore, developing a novel alloy material and its preparation method that can comprehensively meet the above performance requirements is of significant clinical importance for improving the long-term efficacy and safety of internal fixation therapy for joints. Summary of the Invention

[0007] To address the problem that existing clinically commonly used metallic materials cannot simultaneously meet multiple performance requirements such as high strength, low modulus, high corrosion resistance, and lightweight, this invention provides a high-strength, lightweight, corrosion-resistant medium-manganese steel, its preparation method, and its applications.

[0008] To solve the above-mentioned technical problems, the technical solution provided by the embodiments of the present invention is as follows: In a first aspect, the present invention provides a high-strength, lightweight, corrosion-resistant medium-manganese steel, the composition by weight percentage of which is: C 0.10%~0.30%, Mn 11.0%~13.0%, Al 2.5%~3.5%, Cu 1.5%~2.5%, Ni 2.5%~3.5%, Mo 0.05%~0.10%, Ti 0.05%~0.10%, V 0.08%~0.12%, P≤0.012%, S≤0.008%, with the balance being Fe and unavoidable impurities.

[0009] Compared to existing technologies, the high-strength, lightweight, corrosion-resistant medium-manganese steel provided by this invention uses Fe as the matrix and achieves a comprehensive balance of lightweight, ultra-high strength, high toughness, and excellent corrosion resistance by precisely controlling the contents of C, Mn, Al, Cu, Ni, and microalloying elements Ti, Mo, and V. The role of each element and the design principle of its content are as follows: (1) Carbon is the main solid solution strengthening element and plays an important role in the stability of austenite. When the carbon content is below 0.10%, the solid solution strengthening effect is insufficient and the stability of austenite decreases; when it is above 0.30%, carbides are easily formed during hot working or welding, which impairs the toughness and formability of the material and may induce intergranular corrosion. This invention controls the carbon content between 0.10% and 0.30%, which ensures both strength and structural stability, while also taking into account the processability.

[0010] (2) Manganese is a strong austenite stabilizing element, which can ensure the formation of a large amount of austenite structure at room temperature, providing a basis for the formation of reverse austenite in subsequent heat treatment. At the same time, Mn can also improve the corrosion resistance of materials. When the manganese content is below 11.0%, the austenite stability is insufficient; when it is above 13.0%, it is easy to cause component segregation, increase costs, and may promote the formation of harmful phases.

[0011] (3) Aluminum has a low density (approximately 2.7 g / cm³). 3 Al (Al) effectively reduces the overall density of the alloy, making it a key element for achieving lightweighting. In addition, Al improves the material's oxidation resistance and strength. When the aluminum content is below 2.5%, the lightweighting effect is not significant; above 3.5%, it may lead to deterioration of hot workability and a decrease in toughness.

[0012] (4) During the aging process, copper can precipitate nanoscale ε-Cu phases. These uniformly distributed nano-precipitates can produce a significant precipitation strengthening effect, improving the strength of the material. At the same time, Cu can also improve corrosion resistance. When the copper content is less than 1.5%, the strengthening effect is insufficient; when it is more than 2.5%, the risk of hot working brittleness increases. In addition, after long-term implantation in the human body environment, copper ions can be continuously and slowly released from the above-mentioned nanoscale ε-Cu phases. These positively charged Cu ions can destroy the cell wall / membrane of bacteria, bind to enzymes in the bacteria to inactivate them, and catalyze the production of a large amount of reactive oxygen species, leading to bacterial death. This endogenous and long-term antibacterial ability can effectively reduce the risk of infection around the implant, which is of vital clinical significance for promoting bone healing and improving the success rate of surgery.

[0013] (5) Nickel, as an austenite stabilizing element, assists Mn in stabilizing austenite and significantly improves the corrosion resistance of materials in physiological environments. Ni can also work synergistically with Cu to reduce the tendency of hot brittleness caused by Cu.

[0014] (6) Titanium mainly forms fine carbonitrides (Ti(C,N)) during processing and heat treatment, which effectively pins grain boundaries and inhibits grain growth, thereby achieving significant grain refinement. This not only improves the strength of the material, but also improves its toughness, enabling the material to resist fracture when subjected to high loads.

[0015] (7) The addition of molybdenum plays a dual role: on the one hand, Mo atoms dissolve in the matrix to generate solid solution strengthening and promote the formation of fine precipitates during aging, contributing additional precipitation strengthening; on the other hand, it can significantly enhance the pitting resistance of the material in the physiological environment containing chloride ions and stabilize the passivation film on the material surface, which is crucial for ensuring the long-term chemical stability and biocompatibility of implants in complex body fluid environments.

[0016] (8) Vanadium mainly refines grains by forming nanoscale carbides (VC), and works in synergy with the strengthening mechanisms of Ti and Mo to improve the strength and toughness matching of the material, so that the material has both high strength and good plasticity and toughness, thus effectively coping with dynamic and impact loads in human activities.

[0017] Secondly, the present invention also provides a method for preparing the above-mentioned high-strength, lightweight, corrosion-resistant medium-manganese steel, comprising the following steps: S1, the steelmaking raw materials are smelted and cast to obtain steel ingots; the steel ingots are homogenized and forged into billets to obtain casting billets; the casting billets are hot rolled and water-cooled to obtain hot-rolled plates. S2, Under an inert atmosphere, the hot-rolled plate is annealed at 590℃~610℃. After annealing, it is cooled in the furnace to below 300℃ and then air-cooled to obtain the annealed plate. S3, the annealed plate is subjected to high-frequency pulse current treatment, water cooling, and then ultrasonic impact treatment to obtain high-strength, lightweight, corrosion-resistant medium manganese steel. In the high-frequency pulse current processing, the angle between the normal to the surface of the annealing plate and the direction of the pulse current is 0°~45°.

[0018] The present invention provides a method for preparing high-strength, lightweight, and corrosion-resistant medium-manganese steel. After hot rolling, the billet is rapidly water-cooled to form a martensitic structure. This structure accumulates high distortion energy and internal stress, providing energy reserves for subsequent microstructure optimization. During the annealing stage at 590℃~610℃, dislocations within the martensitic laths recover, forming dislocation walls and cellular structures through slip and recombination, significantly reducing the system energy and providing a clean and stable starting point for subsequent phase transformation control. Furthermore, this temperature range is also a sensitive range for carbide precipitation in medium-manganese steel; fine metastable carbide particles will disperse and precipitate within the supersaturated martensite matrix. This process, on the one hand, achieves pre-distribution of carbon elements, reducing the carbon concentration in the matrix and making the diffusion and distribution of carbon to austenite during subsequent pulsed current treatment easier to control, avoiding microstructure instability caused by abnormal local carbon concentration; on the other hand, it pins the original austenite grain boundaries, inhibiting austenite grain coarsening during subsequent critical zone heating. In addition, the interfaces between these carbides and the matrix, as well as the large-angle subgrain boundaries formed by dislocation recovery, can provide uniformly distributed nucleation sites for reverse-transformed austenite, which helps to form a denser and more stable austenite network. At the same time, they can also "soften" and preliminarily regulate the strong {111}〈110〉 texture after hot rolling and quenching.

[0019] Secondly, high-frequency pulsed current treatment is used to achieve directional optimization of microstructure and texture based on annealing. The electromigration effect generated by the high-frequency pulse can significantly accelerate the diffusion of elements such as C, Mn, and Ni into the retained / newly formed austenite region, promoting the formation of highly enriched stable inverse austenite grains at the original austenite grain boundaries, and constructing a continuous austenite framework. By controlling the angle between the surface normal of the annealed plate and the current direction, the directionality of electron wind is utilized to selectively promote the nucleation and preferential growth of inverse austenite grains with specific orientation relationships, thereby achieving the control of material anisotropy and mechanical properties.

[0020] Finally, ultrasonic impact treatment introduces a gradient nanostructure and high residual compressive stress into the material surface (100-300 μm depth), significantly improving the surface hardness, yield strength, pitting corrosion resistance, and stress corrosion cracking resistance. In particular, it greatly enhances fatigue strength under alternating loads, which is crucial for implants subjected to long-term cyclic stress. Simultaneously, due to the localized treatment, the overall good plasticity of the material is maintained.

[0021] In summary, this invention optimizes the initial microstructure through annealing, uses high-frequency pulsed current to directionally regulate the austenitic framework and texture, and employs ultrasonic nano-strengthening to enhance surface properties. The combination of these three methods results in a final material structure consisting of an equiaxed austenitic framework arranged at the original austenitic grain boundaries, with an internal layered mixed microstructure of fine martensite and inverted austenite. The texture also transforms from an initial strong {111}<110> fibrous texture to a directional texture dominated by {100}<010> cubic texture, effectively reducing material anisotropy and achieving high overall performance. The medium-manganese steel prepared by this method exhibits excellent mechanical properties, biocompatibility, long-term service reliability, and performance designability, providing an effective solution to the problem of balancing strength, modulus, corrosion resistance, fatigue resistance, and lightweight in existing orthopedic implant materials.

[0022] Specifically, in S1, a vacuum induction furnace is used to melt the raw materials, and the molten steel obtained is cast into steel ingots using a casting process known in the art.

[0023] Furthermore, in S1, the homogenization treatment is carried out at a temperature of 1150℃~1200℃ for a time of 1.5h~2.0h.

[0024] The above homogenization process can effectively eliminate dendritic segregation generated during ingot solidification, ensure uniform distribution of alloying elements in the matrix, thereby avoiding local weak points in performance caused by uneven composition. It also provides a reliable prerequisite for the dispersed precipitation of microalloyed carbonitrides, the uniform austenite inversion transformation, and the final acquisition of a fine-grained structure with consistent performance during subsequent hot working and heat treatment.

[0025] Specifically, in step S1, forging is performed using a forging press or a heavy-duty rolling mill. The deformation per pass is controlled at 20%-30%, and the total forging ratio is ≥3. Periodic turning during operation ensures uniform deformation. The forging temperature for each pass is not lower than 950℃, and the final forging temperature is controlled within the range of 850-900℃ to avoid the formation of mixed-grain structures. The final product is a 100mm × 100mm square billet with cross-sectional dimensional tolerances controlled within ±2mm.

[0026] Furthermore, in S1, the hot rolling temperature is 850℃~950℃.

[0027] Hot rolling is carried out in the fully austenitic region of 850℃ to 950℃. At this temperature, the material has good high-temperature plasticity and can achieve sufficient dynamic recrystallization, thereby significantly refining the initial grains and providing a uniform and fine microstructure starting point for subsequent cooling transformation. At the same time, this temperature can effectively avoid severe work hardening caused by excessively low temperature or abnormal grain growth caused by excessively high temperature, ensuring that the hot-rolled plate has a uniform microstructure and consistent properties, laying a controllable deformation and phase transformation foundation for obtaining an ideal microstructure in subsequent heat treatment.

[0028] Furthermore, in S1, the cooling rate of the water cooling is ≥30℃ / s.

[0029] This cooling rate ensures that the microstructure after hot rolling is mainly composed of supersaturated lath martensite. This not only stores high lattice distortion energy and internal stress, providing sufficient driving force for recovery, recrystallization, and carbide dispersion precipitation in the subsequent annealing process, but also the supersaturated solid solution carbon reserves the necessary carbon atoms for the subsequent formation of reverse-transformed austenite. Therefore, this rapid cooling is a key prerequisite for obtaining the final framework + layered fine dual-phase microstructure.

[0030] Specifically, in S1, the thickness of the hot-rolled plate is 3mm to 5mm.

[0031] Furthermore, in S2, the annealing time is 1h to 2h.

[0032] An optimal annealing time ensures that the martensitic matrix completes a full recovery process and promotes the uniform and stable formation of reverse-transformed austenite in the ferrite matrix. Simultaneously, it provides sufficient time for the diffusion and redistribution of carbon and alloying elements, which is beneficial for the dispersed precipitation of nanoscale reinforcing phases (such as ε-Cu phase). Too short a time may lead to insufficient microstructure transformation or uneven element distribution; too long a time may cause coarsening of austenite or precipitated phases, impairing the overall properties of the material.

[0033] It should be noted that the inert atmosphere described in this invention is provided by conventional inert gases in the art, such as nitrogen and argon. This invention does not impose any special limitations; any gas that can prevent surface oxidation of the material during the annealing and heat preservation process is acceptable.

[0034] Furthermore, in S3, the pulse frequency of the high-frequency pulse current processing is 10kHz~50kHz, and the current density is 50A / mm². 2 ~200A / mm 2 The processing time is 5s to 30s.

[0035] The high frequency and current density can rapidly and uniformly heat the material to the critical temperature (710~750℃) in a very short time, generating strong electromigration and electroplastic effects. This greatly promotes the directional diffusion of austenite-stabilizing elements such as C and Mn, thereby rapidly and uniformly forming a high volume fraction of reverse-transformed austenite. Simultaneously, the extremely short processing time effectively avoids austenite grain coarsening and the precipitation of harmful phases such as κ-carbides caused by prolonged high-temperature holding, thus preserving a fine-grained structure and ensuring the material's strength, toughness, and stability.

[0036] Furthermore, in the high-frequency pulse current processing, the angle between the normal to the surface of the annealing plate and the direction of the pulse current is 0°.

[0037] It should be noted that by precisely controlling the angle between the pulsed current direction and the sample surface normal, the active design and optimization of the material's internal texture (crystal orientation) can be achieved. Specifically, when the angle is set to 0° (i.e., the current direction is perpendicular to the sample surface), the directional effect of the electron wind is most significant, which can most effectively promote the preferential growth of crystal nuclei with specific orientation relationships, thereby inducing the formation of strong {100} <010> The cubic texture helps reduce the mechanical anisotropy of the material and improves its overall plastic forming ability. When the included angle is adjusted to 45°, it helps to enhance {110}. <001> Gaussian texture components may promote a more uniform distribution of multiple texture components, thereby optimizing the strength and toughness matching of materials in specific directions, or obtaining more balanced comprehensive performance.

[0038] The angle between the annealing plate and the pulsed current can be set using a precision sample clamp equipped with angle calibration and fixing functions. This clamp can securely fix the sample in the preset spatial orientation, ensuring that the angle between the pulsed current direction and the sample surface normal meets the set requirements during high-frequency pulsed current treatment. Specifically, a series of dedicated clamps for the Gleeble thermal simulation testing machine produced by Thermcraft Corporation (USA) or similar domestic high-temperature testing equipment suppliers can be used.

[0039] Furthermore, in S3, during the ultrasonic impact treatment, the angle between the normal to the surface of the annealed plate and the ultrasonic impact head is 70°~90°.

[0040] The impact angle is a key parameter determining the plastic strain path and the type of defects introduced into the surface layer. The most suitable impact mode can be selected based on the expected stress state of the final implanted device. Specifically: When a 90° vertical impact is used, the impact energy is efficiently transferred along the normal direction, mainly introducing multiaxial compressive stress and severe strain into the surface layer, leading to extremely fine grains and strong randomization of the texture. This is suitable for applications requiring high surface hardness, high residual compressive stress, and isotropy. When a 70°~80° inclined impact is used, significant shear strain components are superimposed while introducing nanocrystals, which can induce specific shear textures (such as {110}) on the surface layer. <001> (Iso-shear texture), which enables customized enhancement of the implant's fatigue resistance, yield strength, and resistance to stress corrosion cracking in key directions based on the principal stress direction of the implant at a specific location in the body.

[0041] For orthopedic internal fixation devices (such as bone plates and screws) with complex shapes and varying stress states, different impact angles can be used in different locations. This allows for the optimal matching of surface mechanical properties and long-term service reliability without excessively sacrificing the overall plasticity of the material. This provides a key technological guarantee for meeting the demanding and variable mechanical and biological environmental requirements of implants in human joints.

[0042] Furthermore, in S3, the ultrasonic frequency of the ultrasonic impact treatment is 15kHz~25kHz, the amplitude of the impact head is 10μm~50μm, the scanning rate is 100mm / min~500mm / min, and a total of 1~3 cycles are performed, with each cycle taking 2min~3min.

[0043] The combination of high ultrasonic frequency and moderate amplitude can apply high energy density and high strain rate impact to the material surface per unit time, thereby effectively breaking the surface grains and providing sufficient driving force for the formation of gradient nanostructures. The resulting gradient nanostructure surface can significantly improve the surface hardness, yield strength and pitting resistance of the material, while the tissue and property gradient transitioning from the surface to the core can effectively inhibit the initiation and propagation of fatigue cracks and greatly improve the fatigue life of implants. This is crucial for orthopedic internal fixation devices that are subjected to alternating loads for a long time.

[0044] Thirdly, the present invention also provides the application of the above-mentioned high-strength, lightweight, corrosion-resistant medium-manganese steel in the field of orthopedic internal fixation and implant materials.

[0045] The high-strength, lightweight, and corrosion-resistant medium-manganese steel provided by this invention achieves a microstructure composed of a stable austenitic framework and a fine-grained biphase layer through synergistic microalloying design of elements such as Cu, Ti, Mo, and V, combined with two-phase annealing and high-frequency pulsed current treatment. This structure not only provides the material with a good balance of high strength and high toughness but also, by retaining a large amount of metastable austenite, allows the material's elastic modulus to approach that of human bone, effectively mitigating stress shielding effects. Finally, ultrasonic impact treatment introduces a gradient nanostructure and residual compressive stress into the surface layer, significantly improving surface hardness, wear resistance, and fatigue resistance. The medium-manganese steel prepared by this method possesses ultra-high strength, good toughness, an elastic modulus close to that of human bone, excellent resistance to physiological corrosion, and long-lasting antibacterial ability due to the slow release of Cu ions. Its unique microstructure and performance matching makes it particularly suitable for internal fixation devices in joints subjected to complex stresses. While achieving lightweight design, it significantly improves the mechanical reliability, fatigue resistance, and biocompatibility of implants, demonstrating high practical value. Attached Figure Description

[0046] Figure 1 This is a SEM image of the hot-rolled plate prepared in step S3 of Embodiment 1 of the present invention; Figure 2 This is a SEM image of the annealed plate prepared in step S4 of Embodiment 1 of the present invention; Figure 3 This is a SEM image of the workpiece after high-frequency pulsed current processing in step S5 of embodiment 1 of the present invention. Figure 4 This is a SEM image of the workpiece after ultrasonic impact treatment in step S5 of embodiment 1 of the present invention. Figure 5 These are surface pole figures of workpieces at different processing stages in Embodiment 1 of the present invention, wherein (a) is the surface pole figure of the workpiece after hot rolling, (b) is the surface pole figure of the workpiece after annealing, (c) is the surface pole figure of the workpiece after high-frequency pulse current treatment, and (d) is the surface pole figure of the workpiece after ultrasonic impact treatment; (e) to (h) are projections of the grain orientation in the surface pole figures corresponding to (a) to (d) on the stereographic plane; and (i) to (l) are the surface inverse pole figures corresponding to (a) to (d) respectively. Figure 6 The stress-strain curve of the high-strength, lightweight, corrosion-resistant medium-manganese steel prepared in Example 1 of this invention; Figure 7 Tafel curves of high-strength, lightweight, corrosion-resistant medium-manganese steel prepared in Example 1 of this invention. Detailed Implementation

[0047] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0048] To better illustrate the present invention, further examples are provided below.

[0049] Example 1 This invention provides a high-strength, lightweight, corrosion-resistant medium-manganese steel with the following composition by weight percentage: C 0.20%, Mn 12.0%, Al 3.0%, Cu 2.0%, Ni 3.0%, Mo 0.08%, Ti 0.08%, V 0.10%, P 0.011%, S 0.007%, with the balance being Fe and unavoidable impurities.

[0050] The preparation steps for the above-mentioned high-strength, lightweight, corrosion-resistant medium-manganese steel are as follows: S1. Prepare materials according to the above composition design, and melt the raw materials in a vacuum induction furnace to obtain ingots; S2, the ingot is homogenized at 1180℃ for 2 hours, and then forged using a forging press. The deformation amount per pass is 25%, the total forging ratio is 4, the forging temperature of each pass is not lower than 950℃, and the final forging temperature is 850℃, to obtain a square billet with a cross section of 100mm×100mm. S3, the billet is heated to 900℃, held for 1 hour and then hot rolled to a final thickness of 4mm. After rolling, it is immediately water quenched with an average cooling rate of ≥150℃ / s to obtain a hot-rolled plate. S4, the hot-rolled plate is annealed at 600°C in a nitrogen protective atmosphere for 2 hours, and then cooled in the furnace to 250°C before being removed from the furnace and air-cooled to obtain an annealed plate; S5, Place the annealing plate in a high-frequency pulse current processing device, set the pulse frequency to 30kHz, and the current density to 120A / mm². 2 The processing time was 15 seconds, and the surface of the annealing plate was controlled to be perpendicular to the direction of the pulse current. The temperature of the annealing plate was stabilized at 730℃ by an infrared thermometer. After the processing was completed, the plate was cooled to room temperature by water. S6. The surface of the workpiece after high-frequency pulse current treatment is treated with an ultrasonic impact device. The ultrasonic frequency is set to 20kHz, the impact head amplitude is 30μm, and the scanning rate is 300mm / min. A total of 2 cycles are performed, and the treatment time of each cycle is 2min. The ultrasonic impact head is controlled to be perpendicular to the workpiece surface. After the treatment, high-strength, lightweight, corrosion-resistant medium manganese steel is obtained.

[0051] Example 2 This invention provides a high-strength, lightweight, corrosion-resistant medium-manganese steel with the following composition by weight percentage: C 0.10%, Mn 11.0%, Al 2.5%, Cu 1.5%, Ni 2.5%, Mo 0.05%, Ti 0.05%, V 0.08%, P 0.009%, S 0.008%, with the balance being Fe and unavoidable impurities.

[0052] The preparation steps for the above-mentioned high-strength, lightweight, corrosion-resistant medium-manganese steel are as follows: S1. Prepare materials according to the above composition design, and melt the raw materials in a vacuum induction furnace to obtain ingots; S2, the ingot is homogenized at 1150℃ for 2 hours, and then forged using a forging press. The deformation amount per pass is 30%, the total forging ratio is 3, the forging temperature of each pass is not lower than 950℃, and the final forging temperature is 880℃, to obtain a square billet with a cross section of 100mm×100mm. S3, the billet is heated to 850°C, held for 2 hours and then hot rolled to a final thickness of 5mm. After rolling, it is immediately water quenched with an average cooling rate of ≥150°C / s to obtain a hot-rolled plate. S4, the hot-rolled plate is annealed at 590°C in a nitrogen protective atmosphere for 2 hours, and then cooled in the furnace to 300°C before being removed from the furnace and air-cooled to obtain an annealed plate; S5, Place the annealing plate in a high-frequency pulse current processing device, set the pulse frequency to 10kHz, and the current density to 50A / mm². 2 The processing time is 30 seconds, and the surface of the annealing plate is controlled to be perpendicular to the direction of the pulse current. After the processing is completed, the plate is cooled to room temperature with water. S6. The surface of the workpiece after high-frequency pulse current treatment is treated with an ultrasonic impact device. The ultrasonic frequency is set to 15kHz, the impact head amplitude is 10μm, the scanning rate is 100mm / min, and a total of 3 cycles are performed. The treatment time of each cycle is 3min. The ultrasonic impact head is controlled to be perpendicular to the workpiece surface. After the treatment, high-strength, lightweight, corrosion-resistant medium manganese steel is obtained.

[0053] Example 3 This invention provides a high-strength, lightweight, corrosion-resistant medium-manganese steel with the following composition by weight percentage: C 0.30%, Mn 13.0%, Al 3.5%, Cu 2.5%, Ni 3.5%, Mo 0.10%, Ti 0.10%, V 0.12%, P 0.012%, S 0.006%, with the balance being Fe and unavoidable impurities.

[0054] The preparation steps for the above-mentioned high-strength, lightweight, corrosion-resistant medium-manganese steel are as follows: S1. Prepare materials according to the above composition design, and melt the raw materials in a vacuum induction furnace to obtain ingots; S2, the ingot is homogenized at 1200℃ for 1.5h, and then forged using a forging press. The deformation amount per pass is 20%, the total forging ratio is 5, the forging temperature of each pass is not lower than 950℃, and the final forging temperature is 900℃, to obtain a square billet with a cross section of 100mm×100mm. S3, the billet is heated to 950°C, held for 1 hour and then hot rolled to a final thickness of 3mm. After rolling, it is immediately water quenched with an average cooling rate of ≥150°C / s to obtain a hot-rolled plate. S4, the hot-rolled plate is annealed at 610°C in a nitrogen protective atmosphere for 1 hour, and then cooled in the furnace to 280°C before being removed from the furnace and air-cooled to obtain an annealed plate; S5, Place the annealing plate in a high-frequency pulse current processing device, set the pulse frequency to 50kHz, and the current density to 200A / mm². 2 The processing time is 5 seconds, and the surface of the annealing plate is controlled to be perpendicular to the direction of the pulse current. After the processing is completed, the plate is cooled to room temperature with water. S6. The surface of the workpiece after high-frequency pulse current treatment is treated with an ultrasonic impact device. The ultrasonic frequency is set to 25kHz, the impact head amplitude is 50μm, and the scanning rate is 500mm / min. One cycle is performed, and the processing time of each cycle is 2min. The ultrasonic impact head is controlled to be perpendicular to the workpiece surface. After the treatment, high-strength, lightweight, corrosion-resistant medium manganese steel is obtained.

[0055] Comparative Example 1 This comparative example provides a medical-grade 316L stainless steel with the following composition by weight percentage: C 0.02%, Mn 1.5%, Cr 17%, Ni 12%, Mo 2.6%, Si 0.6%, with the balance being Fe and unavoidable impurities.

[0056] The preparation method of the above-mentioned medical-grade 316L stainless steel includes the following steps: S1. Prepare materials according to the above composition design, and melt the raw materials in a vacuum induction furnace to obtain ingots; S2, homogenize the ingot at 1080℃ for 1.5h to obtain medical grade 316L stainless steel.

[0057] Comparative Example 2 This comparative example provides a medium manganese steel with the same chemical composition and content of each component as in Example 1. The only difference between this steel and Example 1 is that the conditions of the S4 annealing step are replaced with annealing at 780°C for 20 minutes. The rest are exactly the same and will not be described in detail here.

[0058] Comparative Example 3 This comparative example provides a medium manganese steel with the same chemical composition and content of each component as in Example 1. The only difference between this and Example 1 is that the high-frequency pulse current treatment step is omitted; otherwise, they are completely identical and will not be described again here.

[0059] Comparative Example 4 This comparative example provides a medium manganese steel with the same chemical composition and content of each component as in Example 1. The only difference between this and Example 1 is that the ultrasonic impact treatment step is omitted; otherwise, they are completely identical and will not be described in detail here.

[0060] Comparative Example 5 This comparative example provides a medium manganese steel with the same chemical composition and content of each component as in Example 1. The only difference between the preparation process and Example 1 is that the angle between the surface normal of the annealing plate and the direction of the pulse current in the high-frequency pulse current treatment step is changed to 60°. The rest is exactly the same and will not be described again here.

[0061] Structural characterization Figure 1 The image shows a SEM image of the hot-rolled plate prepared in step S3 of Example 1. As can be seen from the image, its microstructure is mainly composed of lath martensite, with clearly distinguishable martensite laths and almost no other obvious phases. This microstructure confirms that rapid cooling effectively suppressed diffusion-type phase transformation, resulting in a supersaturated solid solution and high-density dislocations. This provides the necessary microstructure basis and driving force for recovery, carbide precipitation, and the formation of reverse-transformed austenite during subsequent annealing.

[0062] Figure 2 The image shows a SEM image of the annealed plate prepared in step S4 of Example 1. As can be seen from the image, the original martensite structure underwent a significant transformation after annealing, resulting in clearly identifiable blocky equiaxed austenite grains with distinct grain boundary outlines. This indicates that during annealing, some martensite underwent reverse transformation to austenite, accompanied by significant recovery and recrystallization processes. This microstructure provides the necessary microstructural prerequisites and nucleation basis for further stabilization of austenite, texture control, and the final formation of a framework + layered composite microstructure in the subsequent pulsed current treatment stage.

[0063] Figure 3 The image shows the SEM image of the workpiece after high-frequency pulsed current treatment in step S5 of Example 1. As shown in the figure, its microstructure is different from that in the previous stage ( Figure 2 The austenite underwent a further transformation: finer, equiaxed austenite grains were distributed at the original austenite grain boundaries, while the interior consisted of a lamellar mixed structure of martensite and retained austenite (or inverted austenite), with relatively blurred lamellar interfaces. This morphological feature indicates that high-frequency pulsed current treatment, through its unique electro-migration and rapid thermal effects, promoted the inversion transformation, compositional redistribution, and stability enhancement of austenite, thus initially constructing a composite structure of framework (fine equiaxed austenite at grain boundaries) + layer splicing (internal lamellar structure), providing a key microstructure basis for the material to subsequently obtain excellent strength-toughness matching and corrosion resistance.

[0064] Figure 4 The image shows a SEM image of the workpiece after ultrasonic impact treatment in step S5 of Example 1. As shown, the surface microstructure has undergone significant refinement and evolution compared to the previous stage: the fine equiaxed austenite distributed at the original austenite grain boundaries is still visible, while the alternating lamellar austenite and martensite structure within the grains has become clearer and more regular. This indicates that the high strain rate plastic deformation introduced by ultrasonic impact treatment not only refines the surface grains and forms a gradient nanostructure, but also further promotes the interfacial coordination and stability of the dual-phase microstructure, thereby bringing higher hardness, residual compressive stress, and better fatigue and wear resistance to the material surface.

[0065] Figure 5 These are surface pole figures of the workpiece at different processing stages in Embodiment 1 of the present invention. Figure 5 (a) to Figure 5 (d) are the surface pole figures of the samples after four key process stages: (a) after hot rolling, (b) after annealing, (c) after high-frequency pulsed current treatment, and (d) after ultrasonic impact treatment. The colors in the figure refer to the upper right corner band, representing the crystallographic orientation of each grain. For example, the red area indicates that the grain orientation is close to the

[001] direction.

[0066] Figures (e) to (h) show the grain orientations of the corresponding stage pole figures projected onto the stereographic plane, used to characterize the evolution of the overall texture. The values ​​in the figures are distributed according to color bands; the closer to red, the more grains have their normal directions concentrated in the coordinate orientation of that sample.

[0067] Figures (i) to (l) are the inverse pole figures for the corresponding stages, reflecting the orientation distribution of the crystal in crystallographic coordinates. By comparison, it can be seen that obvious red clusters appear in the lower right corner of Figures (i) and (j), indicating that a large number of grains are concentrated in the

[111] direction in this state, forming a typical {111}<110> texture.

[0068] Overall, from (i) to (l) (inverse pole figure), it can be observed that the texture gradually changes from a strong

[111] orientation to a

[001] orientation; from (e) to (h) (pole figure projection), it shows that the texture gradually evolves from a relatively disordered state to a defined {100}<010> cubic texture. The above-mentioned directional evolution of texture confirms that, through pulsed current and ultrasonic impact treatment at a specific angle in the process described in this invention, it is possible to achieve active and controllable regulation of the material texture type.

[0069] Performance testing The samples prepared in Example 1 and Comparative Examples 1 to 5 were used to prepare standard mechanical property test specimens and corrosion test specimens by wire electrical discharge machining. All specimens were polished to mirror cleanliness, and then ultrasonically cleaned with acetone, anhydrous ethanol and deionized oil in sequence, and dried for later use.

[0070] Yield strength, tensile strength, and elongation after forging were tested according to the standard ASTM E8 / E8M - Metallic Materials - Tensile Testing, using a universal testing machine at room temperature and a strain rate of 1×10⁻⁶. -3 s -1 The stress-strain curve of Example 1 is as follows: Figure 6 As shown. The specific strength is calculated using the following formula: Specific strength = Tensile strength (MPa) / Density (g / cm³). 3 ).

[0071] The corrosion resistance was tested according to the standard test method of ASTM G59-97 (2014) for measuring electrodynamic polarization resistance. A standard three-electrode system was used, with the sample under test as the working electrode, a saturated calomel electrode (SCE) as the reference electrode, and graphite as the counter electrode. The electrolyte was a 0.9 wt% NaCl solution at 37 ± 1 °C. The scan started approximately 200 mV below the self-corrosion potential and continued until the current density increased significantly, with a scan rate of 1 mV / s. The obtained Tafel curves are shown below. Figure 7 As shown.

[0072] The test results are shown in Table 1.

[0073] Table 1

[0074] The medium manganese steels prepared in Examples 2-3 above can achieve technical effects comparable to those in Example 1.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. The application of a high-strength, lightweight, corrosion-resistant medium-manganese steel in the preparation of orthopedic internal fixation and implant materials, characterized in that, Its composition by weight percentage is as follows: C 0.10%~0.30%, Mn 11.0%~13.0%, Al 2.5%~3.5%, Cu 1.5%~2.5%, Ni 2.5%~3.5%, Mo 0.05%~0.10%, Ti 0.05%~0.10%, V 0.08%~0.12%, P≤0.012%, S≤0.008%, with the balance being Fe and unavoidable impurities; The high-strength, lightweight, corrosion-resistant medium-manganese steel is prepared by the following method: S1, the steelmaking raw materials are smelted and cast to obtain steel ingots; the steel ingots are homogenized and forged into billets to obtain casting billets; the casting billets are hot rolled and water-cooled to obtain hot-rolled plates. S2, Under an inert atmosphere, the hot-rolled plate is annealed at 590℃~610℃. After annealing, it is cooled in the furnace to below 300℃ and then air-cooled to obtain the annealed plate. S3, the annealed plate is subjected to high-frequency pulse current treatment, water cooling, and then ultrasonic impact treatment to obtain high-strength, lightweight, corrosion-resistant medium manganese steel. In the high-frequency pulsed current processing, the angle between the normal to the annealing plate surface and the direction of the pulsed current is 0° to 45°; the pulse frequency of the high-frequency pulsed current processing is 10kHz to 50kHz, and the current density is 50A / mm². 2 ~200A / mm 2 The processing time is 5s to 30s.

2. The application as described in claim 1, characterized in that, In S1, the homogenization treatment is carried out at a temperature of 1150℃~1200℃ for a time of 1.5h~2.0h.

3. The application as described in claim 1, characterized in that, In S1, the hot rolling temperature is 850℃~950℃.

4. The application as described in claim 1, characterized in that, In S1, the cooling rate of the water cooling system is ≥30℃ / s.

5. The application as described in claim 1, characterized in that, In S2, the annealing time is 1h to 2h.

6. The application as described in claim 1, characterized in that, In S3, during the ultrasonic impact treatment, the angle between the normal to the surface of the annealing plate and the ultrasonic impact head is 70°~90°.

7. The application as described in claim 1, characterized in that, In S3, the ultrasonic frequency of the ultrasonic impact treatment is 15kHz~25kHz, the amplitude of the impact head is 10μm~50μm, the scanning rate is 100mm / min~500mm / min, and a total of 1~3 cycles are performed, with each cycle taking 2min~3min.

Citation Information

Patent Citations

  • Preparation method of high-strength and high-toughness heterogeneous structure drill collar material and drill collar material

    CN112430710A

  • Preparation process of high-quality medium manganese steel stamping part

    CN117840698A

  • High-strength medium manganese steel and preparation method thereof

    CN118389965A